The purposes and attitudes of individuals to use medicinal plants in Turkey - Veysi Acibuca; Nermin Bahsi; Dilek Bostan Budak (Ciência Rural)
ABSTRACT: This study determined the use of medicinal plants as an alternative therapeutic approach in Turkey. Moreover, the study identified the specific ailments for which these plants are employed and the corresponding proportion of usage. Data was collected by face to face interview with using a structured questionnaire form in all regions of Turkey. Both descriptive and inferential statistics were used in data analysis. According to the research findings, approximately 65.4% of participants use medicinal plants into their treatment regime, asserting their significant benefits. Furthermore, it is posited that the consumption of medicinal plants has witnessed an upsurge during the Covid-19 epidemic. The participants’ attitudes towards medicinal plants are directly influenced by their level of knowledge, convenience and perceived usefulness. The study reveals that participants possess awareness of approximately 200 medicinal plants. Among the most well-known plants are garlic (Allium sativum L.), St. John’s Wort (Hypericum perforatum L.), parsley (Petroselinum crispum), chamomile (Matricaria chamomilla L.), ginger (Crocus sativus L.), cloves (Syzygium aromaticum L.), mint (Melissa officinalis L.), thyme (Thymus vulgaris L.), fennel (Foeniculum vulgare Mill.), aloe (Aloe vera L.), linden (Colocasia esculenta L.), nettle (Achillea millefolium L.), and sage (Salvia officinalis L.). The most critical determinant fort he prevalence of medicinal plant consumption appears to be individuals’ positive beliefs regarding their efficacy in curing diseases. Additionally, promoting knowledge about medicinal plants is deemed essential in fostering informed and conscientious consumption practices.